Information Technology for Modern Marketing - T Rohmawati; H Winata (Universitas Komputer Indonesia, 2021)
The purposes of this research are to identify marketing strategies using exposure in the online business world, explain the role and understanding of Exposure in the online marketing business, and explain the marketing system in social media influencers. The method used in this research is descriptive method. The results of this study is that exposure could be one of the best way to promote the product. This study discusses about exposure, influencers' social media, barter exposure, barter exposure system in influencers' social media, and the benefits of doing barter exposure in marketing.